(untitled) (International Educators Conference, 2025)
This thesis analyzes the role of the synergy between quality management systems and technological innovations in ensuring economic and environmental sustainability within agro-industrial clusters. The integrated approach based on standards such as ISO 9001, HACCP, and GlobalG.A.P., combined with technological solutions like agro-ERP, IoT, and GPS monitoring, enables the production of competitive and safe products. By comparing the case of Uzbekistan with international practices, the strategic importance of innovative integration is substantiated. Recommendations include the development of technological infrastructure, capacity building, regulatory compliance, and the establishment of monitoring systems.